Pengaruh Lingkungan Kerja Dan Beban Kerja Terhadap Stres Kerja Guru : Sebuah Kajian Literatur Review - Annissa Fitriani Rizka; Nurhattati Nurhattati; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
Teachers play a crucial role in shaping a quality generation but often face challenges such as work stress. This study aims to analyze the impact of the work environment and workload on teachers' work stress through a literature review using the Systematic Literature Review (SLR) approach. This approach is utilized to collect and review scientific literature related to two main factors: the work environment and workload.The study findings reveal that the work environment significantly influences teachers' stress levels. An unsupportive environment, such as inadequate facilities, uncomfortable classrooms, and poor interpersonal relationships with colleagues and superiors, can increase stress levels. Additionally, workload is another critical factor. The imbalance between teaching time and time for other activities has been proven to increase pressure on teachers.Furthermore, the findings highlight that these two factors interact in influencing work stress. By creating a supportive work environment and ensuring a balanced workload, teachers can work more effectively without being overwhelmed by excessive pressure. Therefore, this study is crucial for understanding and addressing work stress to enhance the quality of education